The Impact of Digitalization via Broadband Expansion on Bank Transparency - Qi Cui; Tianhong Zhao; Tingyue Cui (SAGE Open)
This paper studies the effects of bank digitalization on bank transparency. We propose a novel, time-varying measure of bank digitalization based on variations in broadband access across bank depositors. Our baseline digital measure captures how digital a bank’s customers are using a deposit-weighted access to broadband metric. Analyzing a sample of over 5,800 banks, this paper finds that more digital banks are more transparent. This finding highlights the complementarity between bank digitalization and transparency and has implications for technology-driven financial fragility. We test alternative digitalization measures by taking advantage of variations in the timing of mobile app roll-out for medium and large banks. Using our novel digitalization measure, this paper also shows that larger banks are more digital and that banks are more likely to adopt mobile apps when they become more digital. Furthermore, we document that the positive effect of digitalization on transparency decreases with the size and financial health of the bank, which has important implications for policy aimed at increasing bank transparency. Overall, this paper fills a gap in the literature by documenting the positive impact of digitalization on bank transparency.